HATE SPEECH ON JOKO WIDODO’S OFFICAL FACEBOOK: AN ANALYSIS OF IMPOLITENESS STRATEGIES USED BY DIFFERENT GENDER - Arsen Nahum Pasaribu (Eltin Journal : Journal of English Language Teaching in Indonesia, 2021)
This study aims to reveal how hate speech was realized by netizens of different gender commenting on the Covid-19 pandemic issue posted on the official Facebook fan page of President Joko Widodo. This research was a qualitative descriptive. The research data consisted of 100 netizens’ comments selected from Joko Widodo's Facebook fan page. The data were divided into two categories: 50 comments made by male netizens and 50 comments by female netizens. Data were analyzed based on impoliteness strategies developed by Culpeper. The findings show that male netizens tend to use bold on record impoliteness strategies to express their hatred towards Joko Widodo, followed by positive, negative, and sarcasm impoliteness, respectively. On the other hand, female netizens preferred to use positive impoliteness, negative, sarcasm, and bald on record impoliteness strategies. These findings indicate that male and female netizens differ in expressing their hate speech towards Joko Widodo. Male netizens tend to be clearer, more harsh and straightforward than female ones in expressing their hatred.Keywords: impoliteness, hate speech, speech act, gender, facebook